Construction of a High-Density Genetic Map and Analysis of Seed-Related Traits Using Specific Length Amplified Fragment Sequencing for Cucurbita maxima - Wang, Yunli; Wang, Chaojie; Han, Hongyu; Luo, Yusong; Wang, Zhichao; Yan, Chundong; Xu, Wenlong; Qu, Shuping (Frontiers in Plant Science, 2020)
A high-density genetic map can provide a basis for quantitative trait locus (QTL) mapping and marker-assisted selection (MAS) based on single-nucleotide polymorphisms (SNPs). Specific length amplified fragment sequencing (SLAF-seq) has been successfully applied to construct high-density maps of many species but not Cucurbita maxima. In this study, 100 F2 individuals from two morphologically diverse parents, namely “2013-12” and “9-6”, were used to successfully construct a high-density genetic map of C. maxima using the SLAF-seq method. A total of 8,406 SLAF markers were used to construct a 3,376.87 cM genetic map for 20 linkage groups (LGs) with an average genetic distance of 0.47 cM. With these markers, total ten QTLs for seed-related traits were identified with composite interval mapping (CIM) method. The QTLs affecting seed width (SW), seed length (SL) and hundred-seed weight (HSW) explained a maximum 38.6%, 28.9% and 17.2% of the phenotypic variation and were detected in LG6, LG6 and LG17, respectively. To validate the locations determined by SLAF-seq, additional 150 F2 individuals were used for QTL mapping of SW and SL using cleaved amplified polymorphic sequence (CAPS) markers. The major QTL SL6-1 and SW6-1 locations identified by SLAF-seq overlapped the region identified in the F2 population analysis by the CAPS markers. Based on nonsynonymous SNPs and gene descriptions of the major SW- and SL-associated regions identified by SLAF-seq, we found that the VQ motif, E3 ubiquitin-protein ligase and F-box and Leucine Rich Repeat domains containing protein may play roles in SL and SW in C. maxima. This study reports the construction of the first high-density linkage map of C. maxima by using SNPs developed using SLAF-seq technology. The information obtained from the genetic map is a valuable tool for association mapping of important agronomic traits, map-based gene cloning and MAS-based breeding in C. maxima.